Finite-time flocking of a Cucker-Smale system with external perturbation and intermittent control - Qiming Liu; Jianlong Ren; Shihua Zhang (AIMS Mathematics)
This study presents a modified Cucker-Smale system with external perturbation and intermittent control. First, a new finite-time stability lemma is developed, in which the settling time is determined only by the control interval's duration. Second, by imposing an assumption on external perturbation, the system can achieve collision-avoidance flocking. Third, finite-time flocking is achieved without the sign function, which effectively avoids the undesirable chattering phenomenon in the system. Finally, numerical simulations validate the theoretical analysis, and parameter sensitivity analysis offers important guidance for practical applications such as unmanned aerial vehicle (UAV) formations.